Effective nutrition governance is correlated with better nutrition outcomes in Nepal. - Namirembe, Grace.; Shrestha, Robin.; Mezzano, Julieta.; Ausman, Lynne M.; Davis, Dale.; Baral, Kedar.; Ghosh, Shibani.; Shively, Gerald.; Webb, Patrick. (Tufts University. Tisch Library., 2021)
Keywords: Nutrition governance index, Policy processes, Stunting, Wasting, Nepal.; Springer Open.